Pengaruh Dari Customer Relationship Management (CRM) Terhadap Loyalitas Pelanggan Ada Swalayan, Kota Bogor - Maura Salsabila Kautsar; Agung Prayudha Hidayat; Derry Aditia; Dwi Cahyo Nugroho; Nisa Naillah Rahmawati; Safitri Astiani; Ulya Khoirunisa (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The pursue of this research is to analyze correctional relationship between customer relationship management (CRM) as quality of service and marketing mix to customer loyalty of ADA Swalayan in Bogor. The primary data are collected through questionnaire of 52 respondents who have made transactions in ADA Swalayan and analyzed the data with Structural Equation Modeling (SEM) using software SPSS. The results of the research show that Customer Management Relationship has an influence on customer loyalty of the ADA Swalayan as well.